Double-GEM based thermal neutron detector prototype. (1st September 2022) - Serra Filho, L.A.; Felix dos Santos, R.; de Souza, G.G.A.; Paulino, M.M.M.; Souza, F.A.; Moralles, M.; da Luz, H.N.; Bregant, M.; Munhoz, M.G.; Lai, C.-C.; Höglund, C.; Svensson, P.-O.; et al.
Abstract: The Helium-3 shortage and the growing interest in neutron science constitute a driving factor in developing new neutron detection technologies. In this work, we report the development of a double-GEM detector prototype that uses a 10 B4 C layer as a neutron converter material. GEANT4 simulations were performed predicting an efficiency of (3.14 ± 0.10)%, agreeing within 2.7 σ with the experimental and analytic detection efficiencies obtained by the detector when tested in a 41.8 meV thermal neutron beam. The detector is position sensitive, equipped with a 256+256 strip readout connected to resistive chains, and achieves a spatial resolution better than 3 mm. The gain stability over time was also measured with a fluctuation of about 0.2% h -1 of the signal amplitude. A simple data acquisition with only 5 electronic channels is sufficient to operate this detector.